2013
DOI: 10.1162/jocn_a_00329
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Lifelong Musicianship on Neurophysiological Measures of Concurrent Sound Segregation

Abstract: The ability to separate concurrent sounds based on periodicity cues is critical for parsing complex auditory scenes. This ability is enhanced in young adult musicians and reduced in older adults. Here, we investigated the impact of lifelong musicianship on concurrent sound segregation and perception using scalp-recorded ERPs. Older and younger musicians and nonmusicians were presented with periodic harmonic complexes where the second harmonic could be tuned or mistuned by 1-16% of its original value. The likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 63 publications
7
30
0
Order By: Relevance
“…Overall, perhaps the strong speech-on-speech perception advantage observed with musicians is not a direct result of better pitch perception, but instead more associated with other factors related to auditory perception, such as better stream segregation, better rhythm perception, or even better auditory cognitive abilities (Zendel and Alain, 2013;Miendlarzewska and Trost, 2014;Carey et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, perhaps the strong speech-on-speech perception advantage observed with musicians is not a direct result of better pitch perception, but instead more associated with other factors related to auditory perception, such as better stream segregation, better rhythm perception, or even better auditory cognitive abilities (Zendel and Alain, 2013;Miendlarzewska and Trost, 2014;Carey et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This musician advantage may be due to better processing of acoustic features, such as pitch or fundamental frequency (F0), which is a primary dimension in music (Micheyl et al, 2006) or better stream segregation (Zendel and Alain, 2013). Alternatively, or perhaps in addition, the advantage could also be due to enhanced auditory cognitive abilities, such as better attention or extended working memory capacity, at least in the auditory modality (Strait et al, 2010;Carey et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For the N1-P2 response, these enhancements were especially evident for spectrally rich sounds (Shahin, Roberts, Pantev, Trainor, & Ross, 2005) or sounds that match the musicians instrument of training (Pantev, Roberts, Schulz, Engelien, & Ross, 2001). An enhancement in musicians for P1 was observed for speech sounds (Musacchia et al, 2008); however, a reduction in P1 has been observed in musicians for single tones, chords, and harmonic complexes (Zendel & Alain, 2013;Kuriki et al, 2006). Accordingly, it is likely that P1 is sensitive to musical training.…”
Section: Introductionmentioning
confidence: 96%
“…Using this type of stimulus, Alain (2009, 2013) demonstrated that musicians can detect smaller levels of mistuning compared with nonmusicians. This enhanced ability to perceptually segregate a mistuned harmonic was paralleled by enhancements to a task-independent ERP known as the object-related negativity and a task-dependent component known as the P400 (Zendel & Alain, 2009, 2013. Once sounds are segregated, they must be tracked over time, and musicians are able to maintain segregated auditory streams in memory longer than nonmusicians (Beauvois & Meddis, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…An example of age-related difficulty parsing simultaneous sounds is demonstrated by older adults' higher thresholds for detecting a mistuned harmonic (Alain et al, 2001;Grube et al, 2003;Zendel and Alain, 2012). Low thresholds for mistuned harmonics are understood to indicate effective sound segregation.…”
Section: Introductionmentioning
confidence: 99%